Abundance of Lipopolysaccharide Heptosyltransferase I in Human Gut Microbiome and Its Association With Cardiovascular Disease and Liver Cirrhosis - Lin, Shujin; Zhang, Hui; Wang, Xueke; Lin, Ting; Chen, Zihan; Liu, Jingfeng; Wang, Jianmin (Frontiers in Microbiology, 2021)
Lipopolysaccharide (LPS) is a potent endotoxin on the outer membrane of gram-negative bacteria. Heptosyltransferase I (HpeI) takes part in the synthesis of LPS. In this study, we first collected the protein sequences of HpeI homologs from the human microbiome. The collected HpeI sequences was classified based on sequence similarity, and seven clusters of HpeI were obtained. Among these clusters, proteins from Cluster 3 were abundant in the human mouth, while Clusters 1, 6, and 7 were abundant in the human gut. In addition, proteins from Cluster 1 were mainly from the order of Enterobacterales, while Cluster 6 and 7 were from Burkholderiales. The correlation analysis indicated that the total abundance of HpeIs was increased in patients with cardiovascular disease and liver cirrhosis, and HpeI in Cluster 1 contributed to this increase. These data suggest that HpeI homologs in Cluster 1 can be recognized as biomarkers for cardiovascular disease and liver cirrhosis, and that reducing the bacterial load in Cluster 1 may contribute to disease therapy.